Countries propose a treaty to end corporate impunity - Hans Wetzels (Africa Renewal, 2019)
When Ecuadorian diplomat Luis Gallegos first proposed a “Binding Treaty on Business and Human Rights,” many countries and environmental activists welcomed the idea with open arms.